2017
DOI: 10.1002/eqe.2911
|View full text |Cite
|
Sign up to set email alerts
|

Low‐seismic damage strategies for infilled RC frames: shake‐table tests

Abstract: Summary Unreinforced masonry (URM) infill panels are widely used as partitions in RC frames and typically considered as non‐structural elements in the design process. However, observations from recent major earthquakes have shown that under seismic excitation, the structural interaction between columns and infill walls can significantly alter the structural behaviour, thus causing catastrophic consequences. The purpose of this research was to propose and test an innovative low seismic damage detailing method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It, thus, remains challenging to design and assess masonry buildings for seismic safety, which often display complex nonlinear dynamic behavior owing to the heterogeneous, anisotropic, and quasi‐brittle material properties. Diagonal or sliding cracks of unreinforced masonry (URM) walls can occur under cyclic in‐plane excitations and lead to severe strength and stiffness degradation 5–8 . Numerous experimental studies, research evidence, and reconnaissance reports of several past earthquakes established that confining elements play a vital role in seismic resistance of masonry walls as well as in‐plane (IP) and out‐of‐plane (OFP) behavior of structures 5,9–12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It, thus, remains challenging to design and assess masonry buildings for seismic safety, which often display complex nonlinear dynamic behavior owing to the heterogeneous, anisotropic, and quasi‐brittle material properties. Diagonal or sliding cracks of unreinforced masonry (URM) walls can occur under cyclic in‐plane excitations and lead to severe strength and stiffness degradation 5–8 . Numerous experimental studies, research evidence, and reconnaissance reports of several past earthquakes established that confining elements play a vital role in seismic resistance of masonry walls as well as in‐plane (IP) and out‐of‐plane (OFP) behavior of structures 5,9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Numerous experimental studies, research evidence, and reconnaissance reports of several past earthquakes established that confining elements play a vital role in seismic resistance of masonry walls as well as in-plane (IP) and out-of-plane (OFP) behavior of structures. 5,[9][10][11][12] Confinement of load-bearing masonry walls can be provided in the forms of toothed/non-toothed tie-columns and lintel beams, 13,14 FRP wrapping, 15 or ductile cementitious composites 16 that can enhance the structural strength, drift capacity, and stability. Tomazevic and Klemenc 4 experimentally verified the seismic performance of confined masonry walls and it was observed that tiecolumns significantly improve the ductility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with steel structure and reinforced concrete structure, concrete-filled steel tubular (CFST) structure is widely used in buildings, bridges, and other structural systems with good plasticity (Cai, 2012; Liu et al, 2011), flexural (Nie et al, 2018), shear capacity (Du et al, 2018b), and fire resistance (Yang et al, 2008; Yu et al, 2010). However, during the construction and service of buildings, dynamic loads, such as earthquakes, explosions, and impact loads, may have major adverse effects on the safety of building structures or even damage (Abdollahzadeh and Faghihmaleki, 2017; Hashemi et al, 2016; Petrone et al, 2017; Zhang et al, 2017). As an important bearing component of CFST structure, it is of great significance to study the behavior of CFST columns under extreme loads especially impact loads.…”
Section: Introductionmentioning
confidence: 99%
“…Then the "strong frame-weak infill" criterion which can form a two-line system of defense and prohibit the brittle shear failure in columns was proposed by Huang [15] for the seismic design of infilled frame structures. Other literature review shows that using isolator subframes or flexible connection between the wall and frame can reduce the wall-frame interaction and improve the seismic performance [16][17][18][19][20][21][22]. In a flexible connection, a gap is left between the wall and the RC frame.…”
Section: Introductionmentioning
confidence: 99%